Channel morphology effect on water transport through graphene bilayers - Liu, Bo (2018)
The application of few-layered graphene-derived functional thin films for molecular filtration and separation has recently attracted intensive interests. In practice, the morphology of the nanochannel formed by the graphene (GE) layers is not ideally flat and can be affected by various factors. This work investigates the effect of channel morphology on the water transport behaviors through the GE bilayers via molecular dynamics simulations. The simulation results show that the water flow velocity and transport resistance highly depend on the curvature of the graphene layers, particularly when they are curved in non-synergic patterns. To understand the channel morphology effect, the distributions of water density, dipole moment orientation and hydrogen bonds inside the channel are investigated, and the potential energy surface with different distances to the basal GE layer is analyzed. It shows that the channel morphology significantly changes the distribution of the water molecules and their orientation and interaction inside the channel. The energy barrier for water molecules transport through the channel also significantly depends on the channel morphology.